On-board measurements of particle emissions from marine engines using fuels with different sulphur content. (February 2016) - Winnes, Hulda; Moldanová, Jana; Anderson, Maria; Fridell, Erik
The approaching marine fuel sulphur regulations will result in reductions in emissions of sulphur oxides to air. Importantly, also particle emissions that impose health risks will be lessened by these regulations. Combustion particles from marine engines are complex mixtures of organic compounds, soot, sulphate, metals and other inorganic species. Their composition and abundance are determined both by fuel and engine characteristics. Health risks from particles are thought to be related to the size of particles and chemical composition of particles which makes particle mass a coarse parameter for indication of how harmful emissions are. This article presents emission measurements conducted on board two ships with a focus on comparing number concentrations of ultrafine particles (Dp <100 nm) in diluted exhaust for three different fuel qualities. The fuels are chosen based on their relevance to existing and coming into force regulations on sulphur in fuel. Implications of these regulations for Sulphur Emission Control Areas on health risks from a shift from heavy fuel oils to low-sulphur marine gas oil are discussed with the measurement results as a basis. The results from the presented measurement emphasise the effect of fuel type on particle formation. The strong relation between sulphur content of fuel and particle emissions is obvious for particle mass but not for particle number and particle sizes.